Webinar Online Literasi Keuangan (Financial Literacy) Bagi Generasi Millennial - Ni Wayan Dian Irmayani; Ni Kadek Sri Mirayani; Ni Wayan Purnami Rusadi (Joong-Ki : Jurnal Pengabdian Masyarakat, 2022)
The purpose of this financial literacy webinar activity is to provide participants with financial literacy skills, and to know the financial literacy abilities of the millennial generation and to increase the understanding of financial literacy of the millennial generation through the provision of webinar material. The material presented is about financial literacy knowledge, financial life cycle, financial financial planning process, scope of financial planning, and application of financial records. The participants were students from the Denpasar National Polytechnic campus, students from several campuses in Bali and outside Bali, high school/vocational high school students from Bali and outside Bali and general public. However, because it is still in the atmosphere of the COVID-19 pandemic, the provision of insight and assessment of insights is carried out online through the Zoom meeting application. There are 122 participants who are willing to take part in this webinar. The importance of knowledge about financial literacy to make the millennial generation financially literate. Financial literacy means understanding how to manage money, paying off debt, insurance, retirement savings, taxes, and financial products such as credit and loans. With a state of financial literacy, the millennial generation can use these financial products to achieve financial prosperity.